Kerjasama Internasional Indonesia dalam Hal Penanganan Pengungsi yang Berada di Wilayah Indonesia Menurut Perspektif Hukum yang Berlaku di Indonesia - Ananda Andika Anjasmara; Tunggal Bayu Laksono; Arka Feryasa; Jodi Junior Palandi (Jurnal Indonesia Sosial Sains, 2021)
The existence of refugees who come from various countries is an international phenomenon whose presence cannot be avoided by countries in the world. Indonesia as a country that is not a party to the Geneva Convention 1951 on Refugees has also experienced the impact of the presence of refugees in the territory of Indonesia. The handling of refugees in Indonesia is carried out by collaborating between the Government of Indonesia and international organizations such as the United Nations High Commissioner for Refugees and with the International Organization for Migration. This study aims 1) Knowing about the handling of refugees in Indonesia in terms of the prevailing laws and regulations in Indonesia 2) Knowing the active role played by the Government of Indonesia with international organizations, especially UNHCR and IOM in terms of handling refugees originating from outside the territory of Indonesia. This research was conducted using a qualitative - descriptive method to provide an overview of the handling of refugees in Indonesia by the Government of Indonesia. The results of this research are put in the form of a conclusion which focuses on the implementation of the handling of refugees in Indonesia that has been carried out in order to uphold values ​​related to human rights. undangan yang berlaku di Indonesia 2) Mengetahui peran aktif yang dilakukan oleh Pemerintah Indonesia dengan Organisasi Internasional khususnya UNHCR dan IOM dalam hal penanggulangan terhadap para pengungsi yang berasal dari luar wilayah Indonesia. Penelitian ini dilakukan dengan metode kualitatif - deskriptif untuk memberikan gambaran tentang penanganan pengungsi di Indonesia oleh Pemerintah Indonesia. Hasil penelitian ini dituangkan dalam bentuk kesimpulan yang mana berfokus pada pelaksanaan penanganan pengungsi di Indonesia yang telah dilakukan guna menegakkan nilai- nilai yang berkaitan dengan hak asasi manusia.